Otto von Gierke (1841–1921) Life and Work of the Great German Lawyer - Martinek, Michael (Pravni zapisi, 2013)
This contribution recalls the life and works of Otto Friedrich von Gierke, who was born in 1841 in Stettin (Prussia) and deceased in 1921 in Berlin and who is unreservedly acknowledged as one of the leading representatives of the Germanistic school of historical jurisprudence, as opposed to the Romanist theoreticians of 19th century juridical scholarship in the wake of F.C. von Savigny. In his career as a legal scholar and a law professor, von Gierke moved from Breslau (1871–1884) to Heidelberg (1884–1887) and finally to Berlin (1887–1921). His remarkable importance rests on his outstanding achievements in his jurisprudential research and thought in a manifold variety of subject matters as well as on the sheer multitude of publications.   The present article resumes von Gierke’s biographical data and facts. Afterwards, it aims at an introduction and explanation of von Gierke’s probably most admirable achievement and success, namely his “organic theory”, according to which the ideal and desirable state organisation should consist of a network of co-operating associations and of subordinate groups. In his extensive writings von Gierke put special emphasis on the voluntary nature of constituting an association. His preference for the establishment of societal and economic life and order based on groups of individuals contributed to the theoretical foundations of decentralized political-administrative systems.   The following chapters are devoted to summarising descriptions of others of his major works, for instance his contributions to the German Lawyers’ Association on question of legal education. Famous are his writings on the first draft of the German Civil Code, promulgated in 1888. Indeed, von Gierke was one of the sharpest critics of the “individualistic” and “Roman” first draft of the code. His observations and annotations initiated a considerable degree of improvements in the following legislative procedures, before the final version was set into force in 1900.   Particular attention has been paid to von Gierke’s most noteworthy treatise on Johannes Althusius, a German philosopher of law of the outgoing 16th and the commencing 17th century who was a protagonist of the natural law theory and can also be regarded as an intellectual father of modern federalism. The major works on the Law of Associations (Genossenschaftsrecht) and of German Private Law (DeutschesPrivatrecht) were widely acclaimed and gained enormous influence in and beyond Germany. The scholarly output of von Gierke appears truly brilliant and monumental. Many of his works can be studied today with the same fascination as it was the case in his days about a century ago. Until today von Gierke belongs to the most influential Germanists and socio-economists of Germany. It was him who drew the attention of his time and of his successors to the social impacts of the law and to the social responsibility of the lawyers. And it was him who prepared the awareness for a fundamental value system as inevitable basis for a country’s legal system. This article invites to read the enlightening works of von Gierke.   Key words: German school, organic theory, theory of legal persons, drafting of the BGB, social theory, pandect law, Johannes Althusius, history of private law.
Keywords: German school; organic theory; theory of legal persons; drafting of the BGB; social theory; pandect law; Johannes Althusius; history of private law.